Automated EPID-based measurement of MLC leaf offset as a quality control tool. (7th February 2018) - Ritter, T A; Schultz, B; Barnes, M; Popple, R; Perez, M; Farrey, K; Kim, G; Moran, J M
Abstract: The multi-leaf collimator (MLC) dosimetric leaf gap (DLG) offset and transmission are measured parameters which influence the dosimetric accuracy of radiation therapy treatment plans. An international consortium developed an efficient method of automatically measuring the two-dimensional MLC DLG and transmission using the electronic portal imaging device (EPID) on multiple Varian TrueBeam linacs incorporating Millennium and high definition (HD) MLCs. Quality control was implemented as part of each test. Results were compiled including comparisons to baseline measurements and between machines. Validations were accomplished using ion chambers (IC) and a 2D IC array. Sensitivity was investigated by introducing deliberate leaf position offsets, repeatability was assessed, and performance was analyzed using statistical process control methods. The EPID measured DLG (EDLG) and transmission were consistently smaller than the IC measured DLG and transmission for all machines tested. EDLG variations across two dimensions averaged more than 0.24 mm for both Millennium and HD MLCs, demonstrating that leaf-to-leaf DLG variations should be assessed for both MLC types. The two-dimensional correlation coefficient between the IC array and EPID measurements was at least 0.937. A nearly linear relationship between changes in the EPID measured leaf gap and actual leaf positions was measured, with R 2 > 0.999. EDLG results were analyzed as a difference relative to a baseline EDLG measurement for each machine, a metric we labeled the leaf offset constancy (LOC). The maximum change in LOC out of the 20 repeatability tests was −0.094 mm. The LOC QC process was found to be capable ( C pk > 1) for 4 machines using a ± 0.15 mm specification limit. LOC results showed that leaves may deviate from their reference positions at a level that approaches dosimetric significance for small stereotactic and highly modulated treatment fields, with average excursions measuring up to 0.21 mm for a Millennium MLC and 0.16 mm for a HD MLC. The effects of initialization, gantry angle, and common repairs are also reported.